CROSSFIT – mental training. Case study - Rolak, Beata; Budnik-Przybylska, Dagmara (Journal of Education, Health and Sport, 2017)
Introduction: CrossFit is a challenging sport. It enforces full engagement of the athlete in every move during every training session. CrossFit teaches perseverance, discipline and respect. Sports psychology allows for in-depth analysis of trainings or competitions. The athlete can better prepare himself for what he may face, both on the mistakes made and on success. Regular mental training supports the athlete's ability to be successful in sports. The aim of the study: The purpose of this paper was to demonstrate the relationship between mental training - here mainly focused on concentration, self-confidence and imagery, CrossFit and sports performance. Material and the method: This paper is a case study. The subject of the study was a male - 30 years old, training crossfit, with the 3-year training experience. Meeting period with the subject male was conducted for 2 months. Before and after the meeting period there were used below mentioned methods: Sports Confidence Inventory (TSCI-PL); The Sport Anxiety Scale (SAS); The Imagination in Sport Questionnaire; The Sport Orientation Questionnaire (SOQ) and the profile of skills. Results: There was a noticeable increase of the results in the questionnaires: Sports Confidence Inventory (TSCI-PL); The Imagination in Sport Questionnaire; The Sport Orientation Questionnaire (SOQ) questionnaire for the self-confidence (TSCI-PL). The Sport Anxiety Scale (SAS) there was an increase of the results regarding the somatic anxiety and worrying also there was a decrease in the scale of distraction. Conclusion: The meeting period turned out to be effective, however the mental training requires regularity and longevity in order to maintain consistency and repeatability of behavior.